Associations between body mass index and molecular subtypes as well as other clinical characteristics of breast cancer in Chinese women - Chen FY; Ou HY; Wang SM; Wu YH; Yan GJ; Tang LL (Dove Medical Press, 2013)
Fei-Yu Chen, Hui-Ying Ou, Shou-Man Wang, Yu-Hui Wu, Guo-Jiao Yan, Li-Li Tang Department of Breast Surgery, Xiangya Hospital, Central South University, Changsha City, Hunan Province, People's Republic of China Background: Several studies have shown a positive association between body mass index (BMI) and the development of hormone receptor-positive breast cancer in postmenopausal women; however, the associations between BMI groups and molecular subtypes have yet to be well defined in premenopausal breast cancer patients. Methods: A total of 2465 female breast cancer patients diagnosed at our institution were recruited for this study. Clinicopathologic information (including age, body height and weight, as well as tumor subtypes and stages) was collected; analyses of these characteristics and the associations between them were performed. Results: A total of 1951 cases were included in the study. The mean age was 47.3 years, the majority of patients were of normal weight, premenopausal, had stage 2 cancer, and did not present with positive nodes. The prevalence of the luminal A, luminal B, human epidermal growth factor receptor 2+, and triple-negative subtypes were 57.8%, 11.6%, 6.1%, and 24.5%, respectively. There were significant differences in the clinicopathologic features among BMI groups in premenopausal patients. The case-only odds ratio (OR) analysis revealed that normal weight patients tended to have luminal B cancer (OR = 1.4, P = 0.206), and overweight and obese patients tended to have triple-negative cancer in premenopausal patients (OR = 2.8, OR = 3.7, respectively; P < 0.001). Conclusion: In Chinese women, breast cancer came with these characteristics: young mean age (premenopause), luminal A subtype, and the majority of them were within a normal weight range. In premenopausal patients, underweight patients tended to have luminal A, lower human epidermal growth factor receptor 2+ expression, stage 1 and no positive node cancer. However, overweight and obese patients tended to have a triple-negative, stage 3, and lymph node metastatic cancer. Keywords: breast cancer, body mass index, molecular subtype, Chinese